2016
DOI: 10.1186/s12889-016-3869-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the implementation process of a participatory organizational level occupational health intervention in schools

Abstract: BackgroundThe importance of process evaluations in examining how and why interventions are (un) successful is increasingly recognized. Process evaluations mainly studied the implementation process and the quality of the implementation (fidelity). However, in adopting this approach for participatory organizational level occupational health interventions, important aspects such as context and participants perceptions are missing. Our objective was to systematically describe the implementation process of a partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(69 citation statements)
references
References 54 publications
1
53
0
Order By: Relevance
“…This is not surprising because it is difficult and sometimes even unethical to perform RCT at the workplace level, and the complexity of many workplace interventions and contexts render RCT unfeasible in the real world. Other alternative designs for the evaluation of occupational health interventions have recently been proposed (83). Tompa et al (5) also reviewed the literature and used a "best evidence" synthesis to assess the strength of evidence.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising because it is difficult and sometimes even unethical to perform RCT at the workplace level, and the complexity of many workplace interventions and contexts render RCT unfeasible in the real world. Other alternative designs for the evaluation of occupational health interventions have recently been proposed (83). Tompa et al (5) also reviewed the literature and used a "best evidence" synthesis to assess the strength of evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent exceptions exist, however. A study by Schelvis et al (2016) found that a participatory organizational intervention implemented in two schools was unsuccessful due to poor implementation fidelity and that these could be explained by poor readiness for change, low participation and contextual barriers. In another study, implementation fidelity as well as adaptation to four components of adherence (i.e., content, dose, coverage and timeliness) was evaluated, showing that adaptations were made to all four adherence components on the individual, unit and organizational levels (von Thiele Schwarz, Hasson, & Lindfors, 2015).…”
Section: Implementation Outcomesmentioning
confidence: 99%
“…and 3) participants' mental models [57,77]. The process components of Themes 2 and 3 may mediate or moderate the link between any intervention exposure and intervention effects [77].…”
Section: Process Evaluation Of the Additional Organisational Health Imentioning
confidence: 99%